PROPRANOLOL HYDROCHLORIDE TOPICAL GEL FOR THE TREATMENT OF INFANTILE HEMANGIOMA - MURALI, MANEESHA; THAYYILAKANDY, SUJAID; P. A., MUHAMMED SHAFI; VENU, ARATHI; SURENDRAN, SARITHA A.; NAIR, SREEJA C. (International Journal of Applied Pharmaceutics, 2020)
Objective: To formulate and evaluate propranolol hydrochloride topical gel for overcoming the limitations and low oral bioavailability associated with conventional therapy. Methods: The propranolol hydrochloride topical gels were prepared by the cold mechanical method. The preliminary evaluation and further characterisation studies was conducted to find the optimised formulation. The in vitro release and ex vivo permeation studies were investigated. The histopathological studies and stability studies was also assessed. Results: The propranolol hydrochloride topical gel was successfully prepared. The in vitro release of optimized topical propranolol hydrochloride gel formulation (G2) showed the highest cumulative percentage drug release that is, 95.55%±0.15 after 7.5 h. (G2) the formulation showed a higher flux value of 4.61μg/cm2/h. The histopathological study using pig skin revealed that the optimized formulation was found to be safe for topical application. Conclusion: The formulated topical gel containing propranolol Hydrochloride seems to be a promising dosage form for enhanced skin delivery of propranolol hydrochloride in treating Infantile Hemangioma.